An Investigation of Visual Arts Teachers’ Attitudes towards Distance Education in the Time of COVID-19 - Kara, Sema (ISTES Organization, 2021)
In the fight against the 2019 coronavirus disease (COVID-19) pandemic, countries have replaced traditional face-to-face education with distance education as a defense tool. Distance education is not only education and training but also is related to individuals. In today's world, where we are faced with a new development, the conveniences provided by distance education technologies have been used in all areas of education. Therefore, technological developments cause changes in all areas of education systems. These changes affect the quality and functions of art education directly and indirectly. In this study, visual arts teachers’ attitudes towards distance teaching during the COVID-19 pandemic were investigated. For this purpose, the attitudes towards distance education were examined by gender, age and school type variables. The study, which was carried out in the survey model, was carried out with 165 visual arts teachers working in public and private secondary and high schools in Konya, Aksaray, Karaman and Niğde provinces. Distance education attitude scale was used to collect the research data. Findings revealed that visual arts teachers’ attitudes towards distance education were generally negative. In addition, the participating teachers’ attitudes towards distance education differed based on the school type, gender and age variables.
Keywords: 4. Education; 8. Economic growth; 3. Good health